Maths 2 Unit Semester Exam Papers PDF
Document Details
Uploaded by Deleted User
2008
JNTU
Tags
Summary
This is a collection of mathematics past papers, specifically focusing on topics such as matrices, quadratic forms, and characteristic roots from JNTU (possibly from the year 2008). The document contains questions and solutions to problems.
Full Transcript
# Find the Rank of the Matrix ## Example 8 Find the rank of the Matrix, by reducing it to the normal form [JNTU (H) June 2010 (Set No. 3)] ### Solution : Let A = $$\begin{bmatrix} 2 & 1& 3 & 5 \\ 4 & 2 & 1 & 3 \\ 8 & 4& 7 & 13 \\ 8 & 4 & -3 & -1 \end{bmatrix}$$ $$\begin{bmatrix} 2 & 1& 3 & 5 \...
# Find the Rank of the Matrix ## Example 8 Find the rank of the Matrix, by reducing it to the normal form [JNTU (H) June 2010 (Set No. 3)] ### Solution : Let A = $$\begin{bmatrix} 2 & 1& 3 & 5 \\ 4 & 2 & 1 & 3 \\ 8 & 4& 7 & 13 \\ 8 & 4 & -3 & -1 \end{bmatrix}$$ $$\begin{bmatrix} 2 & 1& 3 & 5 \\ 0 & 0 & -5 & -7 \\ 0 & 0 & -5 & -7\\ 0 & 0 & -15 & -21\\ \end{bmatrix}$$ (Applying R₂ - 2R₁, R₃ - 4R₁, R₄ - 4R₁) $$\begin{bmatrix} 2 & 1& 3 & 5 \\ 0 & 0 & -5 & -7 \\ 0 & 0 & 0 & 0\\ 0 & 0 & 0 & 0\\ \end{bmatrix}$$ (Applying R₄ - 3R₂, R₃ - R₂) $$\begin{bmatrix} 10 & 5 & 0 & 4 \\ 0 & 0 & -5 & -7\\ 0 & 0 & 0 & 0 \\ 0 & 0 & 0 & 0 \\ \end{bmatrix}$$ (Applying 5R₁ + 3R₂) $$\begin{bmatrix} 1 & 0 & 0 & 4 \\ 0 & 0 & 1 & -7\\ 0 & 0 & 0 & 0 \\ 0 & 0 & 0 & 0 \\ \end{bmatrix}$$ (Applying $C₁ \implies \frac{C₁}{10}, C₂ \implies \frac{C₂} {5}, C₃ \implies \frac{C₃} {5}$) $$\begin{bmatrix} 1 & 0 & 0 & 0 \\ 0 & 0 & 1 & -7\\ 0 & 0 & 0 & 0\\ 0 & 0 & 0 & 0 \\ \end{bmatrix}$$ (Applying C₂ - C₁, C₄ - 4C₁) $$\begin{bmatrix} 1 & 0 & 0 & 0 \\ 0 & 0 & 1 & 0\\ 0 & 0 & 0 & 0\\ 0 & 0 & 0 & 0 \\ \end{bmatrix}$$ (Applying C₄ +7C₃) $$\begin{bmatrix} 1 & 0 & 0 & 0 \\ 0 & 1 & 0 & 0\\ 0 & 0 & 0 & 0\\ 0 & 0 & 0 & 0 \\ \end{bmatrix}$$ (Applying C₂ → C₃) This is of the form $$\begin{bmatrix} I_2 & O \\ O & O \end{bmatrix} $$ which is in normal form. Rank of A = 2 # Find the characteristic roots of the matrix ## Example 1 Find the characteristic roots of the matrix A = $$\begin{bmatrix} 2 & 2 & 1 \\ 1 & 3 & 1 \\ 1 & 2 & 2 \end{bmatrix}$$ [JNTU 2008, (H) June 2009 (Set No. 4)] ### Solution: Given matrix is A = $$\begin{bmatrix} 2 & 2 & 1 \\ 1 & 3 & 1 \\ 1 & 2 & 2 \end{bmatrix}$$ The characteristic equation of A is |A - λI| = 0 $ \begin{bmatrix} 2-λ & 2 & 1 \\ 1 & 3-λ & 1 \\ 1 & 2 & 2 - λ \end{bmatrix} $ = 0 i.e., $(2-λ)[(3-λ)(2-λ)-2]-2[2-λ-1]+1[2-3+λ]=0$ ⇒ $(2-λ)(λ² - 5λ + 4) - 2 (1 -λ) + (λ - 1) = 0$ ⇒ $(2-λ)(λ² - 5λ + 4) - (λ - 1) = 0$ ⇒ $2λ^2 − 10λ + 8 - λ^3 + 5λ^2 - 4λ -λ + 1 = 0$ ⇒ $-λ^3 + 7λ^2 − 15λ + 9 = 0$ ⇒ $λ^3 - 7λ^2 + 15λ - 9 = 0$ ⇒ $(λ-1)(λ^2 - 6λ + 9) = 0 $ ⇒ $(λ-1)(λ-3)^2 = 0$ :. λ = 1, 1, 3 Hence the characteristic roots of A are 1 , 1, 3. # Reduce Quadratic Form to the Normal Form ## Example 1 Reduce the quadratic form 3x² + 2y² + 3z² - 2xy - 2yz to the normal form by orthogonal transformation. [JNTU (H) Dec. 2011 (Set No. 1)] ### Solution: The matrix A of the quadratic form is $$\begin{bmatrix} 3 & -1 & 0 \\ -1 & 2 & -1 \\ 0 & -1 & 3 \end{bmatrix}$$ Now we shall diagonalize the matrix A by orthogonal transformation. For this, we require the eigen values and eigen vectors. So, we need to find the eigen values and eigenvectors of A. Characteristic equation of A is |A -λI| = 0 $$\begin{bmatrix} 3-λ & -1 & 0 \\ -1 & 2-λ & -1 \\ 0 & -1 & 3-λ \end{bmatrix}$$ = 0 i.e., $(3-λ)[(2-λ)(3-λ)-1] + 1[-1(3-λ)] = 0$ ⇒ $(3-λ)(λ^2 - 5λ + 5) - (3-λ) = 0$ ⇒ $(3-λ)(λ^2 - 5λ + 4) = 0$ ⇒ $(3-λ)(λ-1)(λ-4) = 0$ :. λ = 3, λ = 1, λ = 4, which are all different. **When λ = 3, we have** -y = 0 -x -y -z = 0 -y = 0 :. y = 0, x = -z. The corresponding eigen vector is X₁ = $$\begin{bmatrix} 1\\ 0\\ -1 \end{bmatrix}$$ **When λ = 1, the eigen vector is given by** 2x - y = 0 -x + y - z = 0 -y + 2z = 0 Let z= k so that y = 2k and 2x= 2k ⇒ x= k Then, $$\begin{bmatrix} x\\ y\\ z \end{bmatrix}$$ = $$\begin{bmatrix} k\\ 2k\\ k \end{bmatrix}$$ = k $$\begin{bmatrix} 1\\ 2\\ 1 \end{bmatrix}$$ Thus the corresponding eigen vector is X₂ = $$\begin{bmatrix} 1\\ 2\\ 1 \end{bmatrix}$$ **Similarly for λ = 4, we have the eigen vector is:** X₃ = $$\begin{bmatrix} 1\\ -1\\ 1 \end{bmatrix}$$ We observe that these three vectors are mutually orthogonal. We normalize these vectors and obtain e₁ = $$\begin{bmatrix} 1/\sqrt{2}\\ 0\\ -1/\sqrt{2} \end{bmatrix}$$ , e₂ = $$\begin{bmatrix} 1/\sqrt{6}\\ 2/\sqrt{6}\\ 1/\sqrt{6} \end{bmatrix}$$ , e₃ = $$\begin{bmatrix} 1/\sqrt{3}\\ -1/\sqrt{3}\\ 1/\sqrt{3} \end{bmatrix}$$ Let P = The modal matrix in normalized form = [e₁ e₂ e₃] = $$\begin{bmatrix} 1/\sqrt{2} & 1/\sqrt{6} & 1/\sqrt{3}\\ 0 & 2/\sqrt{6} & - 1/\sqrt{3}\\ -1/\sqrt{2} & 1/\sqrt{6} & 1/\sqrt{3} \end{bmatrix}$$ **Diagonalization:** Since P is orthogonal matrix P⁻¹ = Pᵀ so PᵀAP = D where D is the diagonal matrix. :. D = PᵀAP = $$\begin{bmatrix} 1/\sqrt{2} & 0 & - 1/\sqrt{2}\\ 1/\sqrt{6} & 2/\sqrt{6} & 1/\sqrt{6}\\ 1/\sqrt{3} & - 1/\sqrt{3} & 1/\sqrt{3} \end{bmatrix}$$ $$\begin{bmatrix} 3 & -1 & 0 \\ -1 & 2 & -1 \\ 0 & -1 & 3 \end{bmatrix}$$ $$\begin{bmatrix} 1/\sqrt{2} & 1/\sqrt{6} & 1/\sqrt{3}\\ 0 & 2/\sqrt{6} & - 1/\sqrt{3}\\ -1/\sqrt{2} & 1/\sqrt{6} & 1/\sqrt{3} \end{bmatrix}$$ = $$\begin{bmatrix} 3 & 0 & 0 \\ 0 & 1 & 0 \\ 0 & 0 & 4 \end{bmatrix}$$ = diag[3, 1, 4] The quadratic form will be reduced to the normal form. **Hence the transformed Quadratic form is:** XᵀAX = YᵀDY = $$\begin{bmatrix} y₁& y₂ & y₃ \end{bmatrix}$$ $$\begin{bmatrix} 3 & 0 & 0 \\ 0 & 1 & 0 \\ 0 & 0 & 4 \end{bmatrix}$$ $$\begin{bmatrix} y₁\\ y₂\\ y₃ \end{bmatrix}$$ = 3y₁² + y₂² + 4y₃² by the orthogonal transformation X = PY. i.e., x = (1/√2)y₁ + (1/√6)y₂ + (1/√3)y₃ y = (2/√6)y₂ - (1/√3)y₃ z = (-1/√2)y₁ + (1/√6)y₂ + (1/√3)y₃ # Find the nature of the quadratic form ## Example 2 Find the nature of the quadratic form 2x² + 2y² + 2z² + 2yz. [JNTU (H) Jan. 2012 (Set No. 3), Dec, 2019] ### Solution: Given quadratic form is 2x² + 2y² + 2z² + 2yz Matrix of the quadratic form is A = $$\begin{bmatrix} 2 & 0 & 0 \\ 0 & 2 & 1 \\ 0 & 1 & 2 \end{bmatrix}$$ Characteristic equation of A is $$\begin{vmatrix} 2-λ & 0 & 0 \\ 0 & 2-λ & 1 \\ 0 & 1 & 2-λ \end{vmatrix}$$ = 0 [Expand by R₁] ⇒ (2-λ)[(2-λ)² -1] = 0 ⇒ (2-λ)(λ² - 4λ + 3) = 0 ⇒ (2-λ)(λ - 3)(λ - 1) = 0 :. The roots of the characteristic equation are 1, 2, 3. All the roots are positive. The Q. F. is + ve definite. # Find the Eigen values and Eigen vectors of the matrix ## Example 10 Find the Eigen values and the corresponding Eigen vectors of the matrix $$\begin{bmatrix} 2 & 2 & 0 \\ 2 & 5 & 0 \\ 0 & 0 & 3 \end{bmatrix}$$ [JNTU Sep. 2008, (H) Dec. 2011 (Set No. 2)] ### Solution: Let A = $$\begin{bmatrix} 2 & 2 & 0 \\ 2 & 5 & 0 \\ 0 & 0 & 3 \end{bmatrix}$$ The characteristic equation of 'A' is |A - λI| = 0. i.e., $$\begin{vmatrix} 2-λ & 2 & 0 \\ 2 & 5-λ & 0 \\ 0 & 0 & 3-λ \end{vmatrix}$$ = 0 ⇒ (2-λ)[(5-λ)(3-λ)]-2[2(3-λ)]=0 ⇒ (2-λ)(15-5λ-3λ+λ²)-4(3-λ)=0 ⇒ (2-λ)(λ²-8λ+15)-4(3-λ)=0 ⇒ (2-λ)(λ²-8λ+15)-4(3-λ)=0 ⇒ (2-λ)(λ²-8λ+15)-4(3-λ)=0 ⇒ 2λ² - 16λ + 30 - λ³ + 8λ² - 15λ -12 + 4λ = 0 ⇒ -λ³ + 10λ² - 27λ + 18 = 0 ⇒ λ³ - 10λ² + 27λ - 18 = 0 We observe that λ = 1 is a root. Dividing with (λ -1), we get (λ -1)(λ² - 9λ + 18) = 0 i.e., (λ -1)(λ² - 6λ - 3λ + 18) = 0 i.e., (λ -1)[λ(λ - 6)-3(λ -6)]=0 or (λ -1)(λ - 3)(λ - 6) = 0 ∴ λ = 1, 3, 6 Thus, the Eigen values of 'A' are 1, 3, 6. **Case 1:** The Eigen vector corresponding to λ = 1 is given by $$\begin{bmatrix} 1 & 2 & 0 \\ 2 & 4 & 0 \\ 0 & 0 & 2 \end{bmatrix}$$ $$\begin{bmatrix} x₁ \\ x₂ \\ x₃ \end{bmatrix}$$ = $$\begin{bmatrix} 0 \\ 0 \\ 0 \end{bmatrix}$$ [From (1)] ⇒ x₁ + 2x₂ = 0 2x₁ + 4x₂ = 0 and 2x₃ = 0 ⇒ x₃ = 0 Let x₂ = k. Then (2)x₁+ 2k = 0⇒ x₁ = -2k :. The Eigen vector corresponding to λ = 1 is X₁ = $$\begin{bmatrix} -2\\ 1\\ 0 \end{bmatrix}$$ **Case 2:** The Eigen vector corresponding to λ = 3 is given by $$\begin{bmatrix} -1 & 2 & 0 \\ 2 & 2 & 0 \\ 0 & 0 & 0 \end{bmatrix}$$ $$\begin{bmatrix} x₁ \\ x₂ \\ x₃ \end{bmatrix}$$ = $$\begin{bmatrix} 0 \\ 0 \\ 0 \end{bmatrix}$$ [From (1)] ⇒-x₁ + 2x₂ = 0 ⇒ 2x₂ = x₁ and 2x₁ + 2x₂ = 0 ⇒ x₁ + x₂ = 0 From (3) and (4), we get x₂ = 0 ⇒ x₂ = 0 From (3), we get x₁ = 0 Let x₃ = k. The Eigen vector corresponding to λ = 3 is X₂ = $$\begin{bmatrix} 0\\ 0\\ 1 \end{bmatrix}$$ **Case 3:** The Eigen vector corresponding to λ = 6 is given by $$\begin{bmatrix} -4 & 2 &0 \\ 2 & -1 & 0 \\ 0 & 0 & -3 \end{bmatrix}$$ $$\begin{bmatrix} x₁ \\ x₂ \\ x₃ \end{bmatrix}$$ = $$\begin{bmatrix} 0 \\ 0 \\ 0 \end{bmatrix}$$ [From (1)] ⇒-4x₁+2x₂ = 0 2x₁-x₂=0. 2x₁ = x₂ and -3x₃ = 0 Let x₁ = k. Then x₂ = 2x₁ = 2k :. The eigen vector corresponding to λ = 6 is X₃ = $$\begin{bmatrix} 1\\ 2\\ 0 \end{bmatrix}$$ Hence, the Eigen vectors corresponding to λ = 1, 3, 6 are $$\begin{bmatrix} -2\\ 1\\ 0 \end{bmatrix}$$ # Determine the modal matrix P and verify P⁻¹AP is a diagonal matrix. ## Example 2 Determine the modal matrix P of A = $$\begin{bmatrix} -2 & 2 & -3 \\ 2 & -1 & -2 \\ -1 & -2 & -λ \end{bmatrix}$$ and verify P⁻¹AP is a diagonal matrix. ### Solution: The characteristic equation of A is $$\begin{vmatrix} -2-λ & 2 & -3 \\ 2 & -1-λ & -2 \\ -1 & -2 & -λ \end{vmatrix}$$= 0 ⇒ (λ - 5)(λ + 3)² = 0 Thus, the eigen values of A are λ = 5, λ = -3, and λ = -3. **When λ = 5, we have** $$\begin{bmatrix} -7 & 2 & -3\\ 2 & -6 & -2\\ -1 & -2 & -5 \end{bmatrix}$$ $$\begin{bmatrix} x\\ y\\ z \end{bmatrix}$$ = $$\begin{bmatrix} 0\\ 0\\ 0 \end{bmatrix}$$ The corresponding eigen vector is X₁ = $$\begin{bmatrix} 1\\ 2\\ 1 \end{bmatrix}$$ Similarly, for the eigen value λ = -3, we can have two linearly independent vectors X₂ = $$\begin{bmatrix} 2\\ -1\\ 0 \end{bmatrix}$$ and X₃ = $$\begin{bmatrix} 3\\ 0\\ 1 \end{bmatrix}$$ Observe that X₁, X₂ and X₃ are not orthogonal. But they are linearly independent. Consider P = (X₁ X₂ X₃) :. P = $$\begin{bmatrix} 1 & 2 & 3 \\ 2 & -1 & 0 \\ -1 & 0 & 1 \end{bmatrix}$$ = Modal matrix of A. Now det P = 1(-1) - 2(2) + 3(0 -1) = -1 - 4 - 3 = -8 :. P⁻¹ = 1/det P(adj P) = 1/-8 $$\begin{bmatrix} -1 & -2 & 3 \\ 2 & 4 & 6 \\ -1 & -2 & -5 \end{bmatrix}$$ P⁻¹A = (1/-8) $$\begin{bmatrix} -1 & -2 & 3 \\ 2 & 4 & 6 \\ -1 & -2 & -5 \end{bmatrix}$$ $$\begin{bmatrix} -2 & 2 & -3 \\ 2 & -1 & -2 \\ -1 & -2 & -λ \end{bmatrix}$$ = (1/-8) $$\begin{bmatrix} -1 & -2 & 3 \\ 2 & 4 & 6 \\ -1 & -2 & -5 \end{bmatrix}$$ $$\begin{bmatrix} -2 & 2 & -3 \\ 2 & -1 & -2 \\ -1 & -2 & -λ \end{bmatrix}$$ = (1/8) $$\begin{bmatrix} -5 & -10 & 15 \\ -6 & -12 & -18 \\ 3 & 6 & 15 \end{bmatrix}$$ and P⁻¹AP = (1/8) $$\begin{bmatrix} -5 & -10 & 15 \\ -6 & -12 & -18 \\ 3 & 6 & 15 \end{bmatrix}$$ $$\begin{bmatrix} -2 & 2 & -3 \\ 2 & -1 & -2 \\ -1 & -2 & -λ \end{bmatrix}$$ = (1/8) $$\begin{bmatrix} -40 & 0 & 0 \\ 0 & 24 & 0 \\ 0 & 0 & 24 \end{bmatrix}$$ = $$\begin{bmatrix} 5 & 0 & 0 \\ 0 & -3 & 0 \\ 0 & 0 & -3 \end{bmatrix}$$ = diag(5, -3, -3) Hence, P⁻¹AP is a diagonal matrix. # Find nature of the quadratic form, index and signature. ## Example 6 Find nature of the quadratic form, index and signature of 10x² + 2y² + 5z² -4xy -10xz +6yz. [JNTU Aril 2007 (Set No. 4), Sep. 2008 (Set No.1), (H) Dec. 2018] Find the transformation that will transform 10x² + 2y² + 5z² + 6yz − 10zx − 4xy into a sum of squares and find its reduced form. ### Solution: The given quadratic form is 10x² + 2y² + 5z² − 4xy − 10xz + 6yz. Its matrix is given by A = $$\begin{bmatrix} 10 & -2 & -5 \\ -2 & 2 & 3 \\ -5 & 3 & 5 \end{bmatrix}$$ We write A = I₃ AI₃ i.e. $$\begin{bmatrix} 10 & -2 & -5 \\ -2 & 2 & 3 \\ -5 & 3 & 5 \end{bmatrix}$$ = $$\begin{bmatrix} 1 & 0 & 0 \\ 0 & 1 & 0 \\ 0 & 0 & 1 \end{bmatrix}$$ $$\begin{bmatrix} 10 & -2 & -5 \\ -2 & 2 & 3 \\ -5 & 3 & 5 \end{bmatrix}$$ $$\begin{bmatrix} 1 & 0 & 0 \\ 0 & 1 & 0 \\ 0 & 0 & 1 \end{bmatrix}$$ = $$\begin{bmatrix} 10 & -2 & -5 \\ -2 & 2 & 3 \\ -5 & 3 & 5 \end{bmatrix}$$ $$\begin{bmatrix} 1 & 0 & 0 \\ 0 & 1 & 0 \\ 0 & 0 & 1 \end{bmatrix}$$ ⇒ $$\begin{bmatrix} 10 & -2 & -5 \\ 0 & 8 & 10 \\ 0 & 4 & 5 \end{bmatrix}$$ = $$\begin{bmatrix} 1 & 0 & 0 \\ 0 & 1 & 0 \\ 0 & 0 & 1 \end{bmatrix}$$ $$\begin{bmatrix} 1 & 0 & 0 \\ 0 & 1 & 0 \\ 0 & 0 & 1 \end{bmatrix}$$ $$\begin{bmatrix} 10 & 0 & 0 \\ 0 & 2 & 0 \\ 0 & 4 & 1 \end{bmatrix}$$ = $$\begin{bmatrix} 1 & 0 & 0 \\ 0 & 1 & 0 \\ 0 & 0 & 1 \end{bmatrix}$$ $$\begin{bmatrix} 1 & 0 & 0 \\ 0 & 1 & 0 \\ 0 & 0 & 1 \end{bmatrix}$$ (Applying R₂ → 5R₂ + R₁; R₃ → 2R₃+ R₁) ⇒ $$\begin{bmatrix} 10 & 0 & 0 \\ 0 & 40 & 20 \\ 0 & 20 & 10 \end{bmatrix}$$ = $$\begin{bmatrix} 1 & 0 & 0 \\ 0 & 1 & 0 \\ 0 & 0 & 1 \end{bmatrix}$$ $$\begin{bmatrix} 1 & 0 & 0 \\ 0 & 1 & 0 \\ 0 & 5 & 1 \end{bmatrix}$$ $$\begin{bmatrix} 10 & 0 & 0 \\ 0 & 2 & 0 \\ 0 & 4 & 2 \end{bmatrix}$$ = $$\begin{bmatrix} 1 & 0 & 0 \\ 0 & 1 & 0 \\ 0 & 0 & 1 \end{bmatrix}$$ $$\begin{bmatrix} 1 & 0 & 0 \\ 0 & 1 & 0 \\ 0 & 5 & 1 \end{bmatrix}$$ (Applying C₂ → 5C₂ + C₁; C₃ → 2C₃ + C₁) ⇒ $$\begin{bmatrix} 10 & 0 & 0 \\ 0 & 40 & 20 \\ 0 & 100 & 20 \end{bmatrix}$$ = $$\begin{bmatrix} 1 & 0 & 0 \\ 0 & 1 & 0 \\ 0 & -1 & 1 \end{bmatrix}$$ $$\begin{bmatrix} 1 & 0 & 0 \\ 0 & 1 & 0 \\ 0 & 5 & 0 \end{bmatrix}$$ $$\begin{bmatrix} 1 & 0 & 0 \\ 0 & 1 & 0 \\ 0 & 4 & 1 \end{bmatrix}$$ = $$\begin{bmatrix} 1 & 0 & 0 \\ 0 & 1 & 0 \\ 0 & -1 & 1 \end{bmatrix}$$ $$\begin{bmatrix} 1 & 0 & 0 \\ 0 & 1 & 0 \\ 0 & 5 & 0 \end{bmatrix}$$ (Applying R₃ → 2R₃ - R₂) ⇒ $$\begin{bmatrix} 10 & 0 & 0 \\ 0 & 40 & 20 \\ 0 & 0 & 20 \end{bmatrix}$$ = $$\begin{bmatrix} 1 & 0 & 0 \\ 0 & 1 & 0 \\ 0 & -1 & 1 \end{bmatrix}$$ $$\begin{bmatrix} 1 & 0 & 0 \\ 0 & 1 & 0 \\ 0 & 5 & -5 \end{bmatrix}$$ $$\begin{bmatrix} 1 & 0 & 0 \\ 0 & 1 & 0 \\ 0 & 4 & 1 \end{bmatrix}$$ = $$\begin{bmatrix} 1 & 0 & 0 \\ 0 & 1 & 0 \\ 0 & -1 & 1 \end{bmatrix}$$ $$\begin{bmatrix} 1 & 0 & 0 \\ 0 & 1 & 0 \\ 0 & 5 & -5 \end{bmatrix}$$ (Applying C₃ → 2C₃ - C₂) Thus, the given quadratic form is reduced into normal form. i.e., D = PAP where D = $$\begin{bmatrix} 10 & 0 & 0 \\ 0 & 40 & 0 \\ 0 & 0 & 20 \end{bmatrix}$$ and P = $$\begin{bmatrix} 1 & 0 & 0 \\ 0 & 1 & -1 \\ 0 & 5 & -5 \end{bmatrix}$$ The linear transformation is X = PY i.e., $$\begin{bmatrix} x\\ y\\ z \end{bmatrix}$$ = $$\begin{bmatrix} 1 & 0 & 0 \\ 0 & 1 & -1 \\ 0 & 5 & -5 \end{bmatrix}$$ $$\begin{bmatrix} y₁\\ y₂\\ y₃ \end{bmatrix}$$ i.e. x = y₁ + y₂ + y₃; y = 5y₂ - 5y₃; z = 4y₃ The given quadratic form is reduced to XᵀAX = (PY)ᵀA(PY) = Yᵀ(PᵀAP)Y = YᵀDY = $$\begin{bmatrix} y₁& y₂& y₃ \end{bmatrix}$$ $$\begin{bmatrix} 10 & 0 & 0 \\ 0 & 40 & 0 \\ 0 & 0 & 20 \end{bmatrix}$$ $$\begin{bmatrix} y₁ \\ y₂\\ y₃ \end{bmatrix}$$ = 10y₁² + 40y₂² Nature of the quadratic form is positive semi-definite (Here r = 2, n = 3, s = 2) Index, s = no. of positive terms in normal form = 2 Signature = 2s - r = 2(2) - 2 = 2. # Using Cayley-Hamilton theorem, find A⁸, if A = $$\begin{bmatrix} 1 & 2 \\ 2 & -1 \end{bmatrix}$$ ## Example 10 Using Cayley-Hamilton theorem, find (i) A⁸, if A = $$\begin{bmatrix} 1 & 2 \\ 2 & -1 \end{bmatrix}$$ (ii) A³, where A = $$\begin{bmatrix} 1 & 2 \\ 3 & 4 \end{bmatrix}$$ [JNTU July-2003] ### Solution: (i) Given A = $$\begin{bmatrix} 1 & 2 \\ 2 & -1 \end{bmatrix}$$ Characteristic equation of A is |A - λI| = 0 i.e. $$\begin{vmatrix} 1-λ & 2 \\ 2 & -1-λ \end{vmatrix}$$ = 0 ⇒ λ² - 5 = 0 By Cayley-Hamilton theorem, A satisfies its characteristic equation. So, we must have A² = 5I. :. A⁸ = 5A⁶ = 5(A²) (A²) (A²) = 5(5I) (5I) (5I) = 625I. This is left as an exercise to the reader. # Verify Cayley-Hamilton theorem for the matrix A = $$\begin{bmatrix} 1 & 2 & -1 \\ 2 & 1 & -2 \\ 2 & -2 & 1 \end{bmatrix}$$ ## Example 11 (i) If A = $$\begin{bmatrix} 1 & 2 & -1 \\ 2 & 1 & -2 \\ 2 & -2 & 1 \end{bmatrix}$$ verify Cayley-Hamilton theorem. Find A⁴ and A⁻¹ using Cayley-Hamilton theorem. [JNTU Sep. 2006 (Set No. 4)] (ii) Verify Cayley-Hamilton theorem for the matrix A = $$\begin{bmatrix} 1 & 2 & -1 \\ 2 & 1 & -2 \\ 2 & -2 & 1 \end{bmatrix}$$ and hence find A⁻¹ ### Solution: Given A = $$\begin{bmatrix} 1 & 2 & -1 \\ 2 & 1 & -2 \\ 2 & -2 & 1 \end{bmatrix}$$ Characteristic equation of A is given by |A - λI| =0 $$\begin{vmatrix} 1-λ & 2 & -1 \\ 2 & 1-λ & -2 \\ 2 & -2 & 1-λ \end{vmatrix}$$ = 0 ⇒ $$\begin{vmatrix} 3-λ & 0 & λ \\ 2 & 1-λ & -2\\ 2 & -2 & 1-λ \end{vmatrix}$$ = 0 ⇒ (3-λ)[(1-λ)²-4]-[-4-2(1-λ)]=0 ⇒ (3-λ)(λ²-2λ-3)-[-4-2+2λ]=0 ⇒ (3-λ)(λ²-2λ-3)+6-2λ = 0 ⇒ 3λ²-6λ-9-λ³+2λ²+3λ+6-2λ=0 ⇒ -λ³+5λ²-5λ-3=0 ⇒ λ³-5λ²+5λ+3=0 i.e., A³ - 5A² + 5A + 3I = O (2) Now A² = $$\begin{bmatrix} 1 & 2 & -1 \\ 2 & 1 & -2 \\ 2 & -2 & 1 \end{bmatrix}$$ $$\begin{bmatrix} 1 & 2 & -1 \\ 2 & 1 & -2 \\ 2 & -2 & 1 \end{bmatrix}$$ = $$\begin{bmatrix} 3 & 6 & -6 \\ 0 & 9 & -6 \\ 0 & 0 & 3 \end{bmatrix}$$ and A³ = $$\begin{bmatrix} 1 & 2 & -1 \\ 2 & 1 & -2 \\ 2 & -2 & 1 \end{bmatrix}$$ $$\begin{bmatrix} 3 & 6 & -6 \\ 0 & 9 & -6 \\ 0 & 0 & 3 \end{bmatrix}$$ = $$\begin{bmatrix} 3 & 24 & -21 \\ 6 & 21 &